Genetic Diversity of the Endangered Endemic Anoa (Bubalus spp): Implication for Conservation - Dwi Sendi Priyono; Dedy Duryadi Solihin; Achmad Farajallah; Bambang Purwantara (HAYATI Journal of Biosciences, 2022)
Anoa is an endemic ungulate in Sulawesi and its status now is endangered because the population continues to decline. Conservation genetics is one of the crucial issues in the anoa conservation strategy and action plan 2013-2022 document, but this genetic data is not yet available. To investigate and provide valuable information for conservation genetics measures, thirteen polymorphic microsatellites were used to analyze 20 adult anoa. Anoa has relatively low genetic diversity within populations (HO = 0.58), and high genetic differentiation among populations (FST = 0157). Although the anoa population has a bottleneck signal (T.P.M: 0.019; P0.05), the bottleneck simulation results show that the loss of genetic diversity is being slow over the next 100 years (9.5%). We provide some recommendations for conservation genetics based on the findings in this paper, including monitoring and genetically mapping for other anoa populations due to bottleneck signals, establishing the founder of the ex-situ population by examining their genetic diversity status, maintaining and increasing the number of individuals in the ex-situ population to genetically safe population size, and managing anoa populations by avoiding inbreeding. In-situ and ex-situ conservation programs should be combined to maintain the genetic diversity of anoa.